Peningkatan Pemahaman Manajemen Waktu Melalui Bimbingan Kelompok Dengan Teknik Problem Solving pada Siswa - Nurhidayati, Diana Dwi (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2016)
The purpose of this study is to determine the increase of time management understanding through group guidance with problem solving techniques. This research is a classroom action research with cross sectional type. The subjects of research were ten students of class VII A SMP Muhammadiyah 4 Yogyakarta taken by purposive sampling technique. Data collection instrument used was in the form of a questionnaire of time management understanding. Data analysis technique to test the effectiveness of group guidance was problem solving technique which is to improve the understanding of time management of SMP students using the Wilcoxon test. The results of data analysis shows a mean of time management understanding before the action of problem solving techniques was 55.30 and the average after problem solving techniques given was 78.60. Wilcoxon test results shows p = 0.005 so that we can conclude that there is an increase of time management understanding of SMP students after using group guidance with problem solving techniques. The results of this study can be useful for guidance and counseling teachers as a consideration material in improving the understanding of studentsâ time management through group guidance services using problem solving techniques.